2017
DOI: 10.1002/slct.201700757
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer of Monomer via Photoisomerization

Abstract: We experimentally report a new photoisomerization mechanism of fluorescence resonance energy transfer (FRET) of monomer via photoisomerization. Firstly, a new photoisomerization was firstly report by us, in which trans, trans-1,4-Diphenyl-1,3-butadiene (tt-DPB) is photoisomerized to D-DPB (D stands for rotating double bond) by rotating double bond, evidenced by the three dimensional (3D) and 2D excitationemission mappings, and firmly supported by theoretical calculations on potential energy surfaces. Secondly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 21 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Concluded that the kinetics of photoisomerization tt‐DPB to D‐DPB are researched and shown in Figure (a) . It was reported that they have two twisted processes in the ct‐DTB isomer, but here, expected that they are tt‐DPB‐>ct‐DPB‐>cc‐DPB in the ground state (see Figure (b)) . Note that the path of photoisomeriaztion can be seen from Figure (d), and the potential barrier of tt‐DPB‐>cc‐DPB (0.128 u) is significant larger than that of tt‐DPB‐>D‐DPB (0.016 au).…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 87%
See 4 more Smart Citations
“…Concluded that the kinetics of photoisomerization tt‐DPB to D‐DPB are researched and shown in Figure (a) . It was reported that they have two twisted processes in the ct‐DTB isomer, but here, expected that they are tt‐DPB‐>ct‐DPB‐>cc‐DPB in the ground state (see Figure (b)) . Note that the path of photoisomeriaztion can be seen from Figure (d), and the potential barrier of tt‐DPB‐>cc‐DPB (0.128 u) is significant larger than that of tt‐DPB‐>D‐DPB (0.016 au).…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 87%
“…also designed the potential energy surface by optimizing the relative dihedral angle of all ground and excited state. Concluded that the kinetics of photoisomerization tt‐DPB to D‐DPB are researched and shown in Figure (a) . It was reported that they have two twisted processes in the ct‐DTB isomer, but here, expected that they are tt‐DPB‐>ct‐DPB‐>cc‐DPB in the ground state (see Figure (b)) .…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 88%
See 3 more Smart Citations